Kisspeptina: efeito na maturação in vitro de ovócitos bovinos - Oliveira, Mayara (2016)
This study aimed to evaluate different concentrations of kisspeptin, as well as the interaction of kisspeptin and FSH/LH in vitro maturation and oocyte competence in cattle. In Experiment 1 was determined the minimum concentration of Kisspeptin (Kp) to be used, and in Experiment 2 was evaluated its interection with FSH and LH. The oocytes were collected in a commercial slaughterhouse and only Grade I oocytes were utilized. The oocytes were cultured in TCM-199 medium with bicarbonate plus 10% FBS, sodium pyruvate (22μg/mL), amikacin (83mg/mL), FSH (0.5μg/mL), with different concentrations of Kp, the treatments were: FSH + 0M Kp-10; FSH + 10-7M Kp-10, FSH + 10-6M Kp-10; FSH + 10-5M Kp-10. In Experiment 2, was used better concentration of Kp found in Experiment 1, the following treatments: no hormones; FSH; FSH + Kp-10; FSH + LH; FSH, LH + Kp-10; Kp-10. The oocyte competence was determined by nuclear maturation, mitochondrial distribution, MitoTracker® Orange CMTMRos fluorescence intensity and DCF. The evaluation of nuclear maturation was made after 24 hours incubation and the oocytes were stained with DAPI to determine the nuclear stage (Germinal Vesicle-GV, Metaphase I-MI and Metaphase II-MII).The mitochondrial distribution was classified as peripheral/semiperipheral and diffuse in clusters/granules, evaluated after stained with the MitoTracker® Orange CMTMRos, and was also identified the intensity of it. To determine the intensity of ROS oocytes were stained with DCF. The statistical analysis was performed by SAS GLIMMIX PROC. In Experiment 1 oocytes matured only with the FSH reached a smaller nuclear maturation when compared to those who were matured with Kisspeptin at different concentrations (FSH:13/33; FSH + 10-7M Kp-10: 28/35; FSH + 10-6M Kp-10:30/34; FSH + 10-5M Kp-10:28/32; P=0,0001). There was no statistical difference in mitochondrial distribution between treatments (P>0.05). The fluorescence intensity of MitoTracker did not differ among treatments (P>0.05). The DCF fluorescence intensity was lower when the concentration of Kp was increased in the medium (FSH:12177726,1; FSH + 10-7M Kp-10:10945982,83; FSH + 10-6M Kp-10:9820536,53; FSH + 10-5M Kp-10:9147016,38; P<0,0001). Based in the Experiment 1 results, the concentration of Kp was determined in 10-7M. In Experiment 2 the mitochondrial distribution was different between treatments, because oocytes matured only with Kp or FSH+LH, reached a oocyte competence greater than those maturated with FSH only or without hormone addition (no hormones:66,66%; FSH:66,66%; FSH + Kp-10:75,86%; FSH + LH:91,17%; FSH, LH + Kp-10:82,85%; Kp-10:91,17%; P<0,05). The no hormones resulted in a lower nuclear maturation than the other treatments (no hormones: 5/18; FSH:18/32; FSH + Kp-10:22/29; FSH + LH:26/33; FSH, LH + Kp-10:26/34; Kp-10:25/34; P=0,0094). The fluorescence intensity of probes MitoTracker and DCF was lower when Kp was added to the maturation medium (no hormones:1228363/540069; FSH:2307984/1395751; FSH + Kp-10:1941890/1114948; FSH + LH:2502145/1722376; FSH, LH + Kp-10:2286173/1467782; Kp-10:1859411/979325 P<0,0001). So this is the first study that shows that Kisspeptin stimulates oocyte maturation without the presence of gonadotropins in the maturation medium.